Carbon Nanotubes: On‐Chip Chemical Self‐Assembly of Semiconducting Single‐Walled Carbon Nanotubes (SWNTs): Toward Robust and Scale Invariant SWNTs Transistors (Adv. Mater. 23/2017). Issue 23 (June 2017) - Derenskyi, Vladimir; Gomulya, Widianta; Talsma, Wytse; Salazar‐Rios, Jorge Mario; Fritsch, Martin; Nirmalraj, Peter; Riel, Heike; Allard, Sybille; Scherf, Ullrich; Loi, Maria A.
Abstract : Polymer side‐chain functionalization with thiol‐containing groups leads to chemical self‐assembly of semiconducting carbon nanotubes on prepatterned gold electrodes. The tubes are self‐assembled on lithographically pre‐defined electrodes thanks to the chemical bond between the thiol groups and the metal used to define the electrodes. This assembly method, discussed by Maria A. Loi and co‐workers in article number1606757 is scalable and robust to mechanical disturbance.